ASSESSMENT OF OXIDATIVE STABILITY OF MICROENCAPSULATED FLAXSEED OIL VIA FREEZE DRYING USING VARIOUS WALL MATERIAL COMBINATIONS - Muhammad Shafqat Rasool; Qamar Abbas Syed; Masood Sadiq Butt; Muhammad Shahid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Flaxseed oil is a rich source of omega-3 fatty acids, particularly alpha-linolenic acid, but its high content of polyunsaturated fatty acids makes it prone to oxidation. This study aimed to enhance the oxidative stability and shelf life of flaxseed oil through microencapsulation using freeze-drying with different combinations of guar gum and whey protein concentrate as wall materials. Emulsions were evaluated for physical stability, viscosity, droplet size, and peroxide value. The resulting powders were assessed for encapsulation efficiency, moisture content, bulk density, morphology, and oxidative stability. The combination of guar gum and whey protein concentrate (1:1 ratio) showed the highest encapsulation efficiency and oxidative stability, confirming its suitability for flaxseed oil encapsulation.